Energy conservation by retrofitting of dwellings - Sánka Imrich; Petráš Dušan (E3S Web of Conferences, 2019)
This article investigates the impact of energy renovation on the indoor environmental quality of apartment building during heating season. The study was performed in one residential building before and after its renovation. Energy auditing and classification of the selected building into energy classes were carried out. Additionally, evaluation of indoor air quality was performed using objective measurements and subjective survey. Thermal environment and concentration of CO2 was measured in bedrooms. Higher concentrations of CO2 was observed in the residential building after its renovation. The concentrations of CO2, in some cases exceeded the recommended maximum limits, especially after implementing of energy saving measures on the building. The average air exchange rate was visible higher before renovation of the building. The current study indicates that large-scale of renovations may reduce the quality of the indoor environment in many apartments, especially in the winter season.